Delayed Cerebral Radiation Necrosis after Neutron Beam Radiation of a Parotid Adenocarcinoma: A Case Report and Review of the Literature. (30th September 2014) - Hong, Christopher S.; Gokozan, Hamza N.; Otero, José J.; Guiou, Michael; Elder, J. Bradley
Abstract : Cerebral radiation necrosis (CRN) is a well described possible complication of radiation for treatment of intracranial pathology. However, CRN as sequelae of radiation to extracranial sites is rare. Neutron beam radiation is a highly potent form of radiotherapy that may be used to treat malignant tumors of the salivary glands. This report describes a patient who underwent neutron beam radiation for a parotid adenocarcinoma and who developed biopsy-confirmed temporal lobe radiation necrosis thirty months later. This represents the longest time interval described to date, from initial neutron radiation for extracranial pathology to development of CRN. Two other detailed case studies exist in the literature and are described in this report. These reports as well as our patient's case are reviewed, and additional recommendations are made to minimize the development of CRN after extracranial neutron beam radiation. Physicians should include the possible diagnosis of CRN in any patient with new neurologic signs or symptoms and a history of head and neck radiation that included planned fields extending to the base of the skull. Counseling of patients prior to neutron beam radiation should include potential neurologic complications associated with CRN and risks of treatment for CRN including neurosurgical intervention.